1991
DOI: 10.1017/s0952523800004855
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and morphological properties of OFF- and ON-center bipolar cells in the Xenopus retina: Effects of glycine and GABA

Abstract: We studied the morphology and center-surround organization of Lucifer Yellow injected OFF- and ON-center bipolar cells in the light-adapted Xenopus retina and the effects of glycine and GABA on their cone-mediated light responses. In both classes of cell, prominent antagonistic surround responses up to 20 mV in amplitude could be evoked without first suppressing the center responses with steady illumination. An additional feature of the light-evoked bipolar cell response was a pronounced (up to –24 mV) delayed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 56 publications
5
34
1
Order By: Relevance
“…The comparison between the puncta enclosed shows that co-localizations between them exist. Scale bar 20 lm ment with the electrophysiological data according to which glycine is involved in the surround responses of both on-and off-bipolar cells in X. laevis retina (Stone and Schu¨tte 1991). Our results are in agreement with the immunocytochemical data of other authors who have also demonstrated glycine receptors in the lower verte- Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The comparison between the puncta enclosed shows that co-localizations between them exist. Scale bar 20 lm ment with the electrophysiological data according to which glycine is involved in the surround responses of both on-and off-bipolar cells in X. laevis retina (Stone and Schu¨tte 1991). Our results are in agreement with the immunocytochemical data of other authors who have also demonstrated glycine receptors in the lower verte- Fig.…”
Section: Discussionsupporting
confidence: 92%
“…A question of interest arose: if the GlyRs in these two kindred types of amphibian retinae differ or not. The results presented here give answer to this question allowing comparison of the GlyRs in the retina of X. laevis with those in the retina of R. ridibunda, two species widely used in electrophysiological experiments (Stone and Schu¨tte 1991;Popova et al 1997Popova et al , 2000.…”
Section: Introductionmentioning
confidence: 78%
“…At the same time, however, GABA in the ON pathway may more efficiently control receptive field, center-surround, and spatial frequency mechanisms than in the OFF pathway in anurans (Bonaventure and Wioland, 1981). This is in agreement with the results of physiological studies that found differential sensitivity of ON and OFF circuitries to GABA and glycine (Bonaventure et al, 1980;Stone and Schü tte 1991).…”
Section: Synapses Of Gabaergic Elementssupporting
confidence: 88%
“…Most of the studies were performed by using one or narrow range of stimulus intensities and the results obtained are contradictory. While some authors reported that GABA diminishes and GABA antagonists (bicuculline, picrotoxin) enhance the light responses of ON bipolar cells (mudpuppy: Miller, Slaughter, & Dick, 1982;Miller et al, 1981), other authors have not obtained any effect of GABA on them (xenopus: Stone & Shutte, 1991). Still other authors suggest that the effect of GABA on the amphibian ON bipolar cells may be related only to the time characteristics of the light responses and not to their amplitude.…”
Section: Discussionmentioning
confidence: 99%
“…Inconsistent results have been obtained also for the GABA effects on the amphibian OFF bipolar cells. Some authors reported that antagonists of ionotropic GABA receptors have no effect on their light responses (mudpuppy: Daniels, 1974;Miller et al, 1981), while other authors reported their suppression under the influence of GABA (Hare & Owen, 1996;Stone & Shutte, 1991) or GABA antagonists picrotoxin and bicuculline (Hare & Owen, 1996). Our results indicate that GABA, released in both the outer and inner plexiform layer in frog retina, acts to diminish the amplitude and speed up the time course of the cone-mediated light responses of both ON and OFF bipolar cells.…”
Section: Discussionmentioning
confidence: 99%